Problematic social networking sites use and online social anxiety: The role of attachment, emotion dysregulation and motives. (March 2023) - Marino, Claudia; Manari, Tommaso; Vieno, Alessio; Imperato, Chiara; Spada, Marcantonio M.; Franceschini, Christian; Musetti, Alessandro
Highlights: Problematic SNS use (PSNSU) and online social anxiety are associated. Attachment anxiety is associated with PSNSU and social anxiety. Emotion dysregulation could be a therapeutic target to reduce problematic behaviors. Coping and conformity are important antecedents of PSNSU and online social anxiety. Abstract: Problematic Social Networking Sites Use (PSNSU) and social anxiety are associated. SNSs users may develop online social anxiety that may become a standalone problem. The present study aims to test the mediating role of emotion dysregulation and motives (coping, conformity, social, and enhancement) between attachment (anxiety and avoidance) and two outcomes (PSNSU and online social anxiety) in an integrated theory-driven model. Self-report questionnaires were completed by 756 SNSs users (50.4 % females; mean age = 28.74 years, SD  = 8.00). Results of the path analysis supported the partial mediating role of emotion dysregulation in the association between attachment anxiety and both the outcomes and the serial mediating role via four and three motives in the association with PSNSU and online social anxiety, respectively. This study highlighted the role of several relational, emotional, and motivational factors that should be taken into account to tackle PSNSU and online social anxiety through clinical and prevention interventions.